2021
DOI: 10.1002/anie.202110748
|View full text |Cite
|
Sign up to set email alerts
|

Stepwise Generation of Mono‐, Di‐, and Triply‐Reduced Warped Nanographenes: Charge‐Dependent Aromaticity, Surface Nonequivalence, Swing Distortion, and Metal Binding Sites

Abstract: The stepwise chemical reduction of am olecular warped nanographene (WNG) having an egatively curved psurface and defined C 80 H 30 composition with Cs metal used as the reducing and complexing agent allowed the isolation of three different reduced states with one,two,and three electrons added to its p-conjugated system. This provided aunique series of nanosized carbanions with increasing negative charge for indepth structural analysis of consequences of controlled electron charging of non-planar nanographenes,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 71 publications
1
10
0
Order By: Relevance
“…The inversion of aromaticity upon reduction was previously observed in different polycyclic aromatic systems such as wrapped nanographenes and nanobelts. [37][38][39] Impor-tantly, these conclusions were supported by all aromaticity descriptors calculated in this study regardless of their nature (Table 5).…”
Section: Chemistry-a European Journalsupporting
confidence: 75%
See 1 more Smart Citation
“…The inversion of aromaticity upon reduction was previously observed in different polycyclic aromatic systems such as wrapped nanographenes and nanobelts. [37][38][39] Impor-tantly, these conclusions were supported by all aromaticity descriptors calculated in this study regardless of their nature (Table 5).…”
Section: Chemistry-a European Journalsupporting
confidence: 75%
“…Similar trend has been previously detected in the sizable wrapped nanographene species, in which one, two, and three electrons were found to be almost exclusively at the central part of the large polyaromatic molecule. [38] It was also observed that such negative charge localization leads to selective coordination of alkali metal ions to the central part of nanographene surface. As alkali metal ions are sensitive to such negatively dense sites, their coordination to the pentacene dianion center should be expected in this work.…”
Section: Chemistry-a European Journalmentioning
confidence: 98%
“…The X-ray analysis of anionic species consisting of pure hydrocarbons has been achieved only recently. [36][37][38][39][40][41][42][43][44] Since only a few examples of reversible redox response systems are available, they are not considered in this review. Heteroatom-containing hydrocarbons are also excluded from this review because the effect of the introduction of heteroatoms on the redox properties has been well-investigated and reported in several papers.…”
Section: Introductionmentioning
confidence: 99%
“…In this review, we focus on examples of succeeding in isolation and structural determination of cationic species based on pure hydrocarbons with aromatic rings and introduce the intrinsic electrochemical and spectroscopic properties of such hydrocarbons. The X‐ray analysis of anionic species consisting of pure hydrocarbons has been achieved only recently [36–44] . Since only a few examples of reversible redox response systems are available, they are not considered in this review.…”
Section: Introductionmentioning
confidence: 99%
“…7 In the early 1990s the development of the ash vacuum pyrolysis (FVP) method enabled materials scientists to evaluate these compounds. [8][9][10][11] This attention to bowl-shaped molecules arises not only from aesthetic pleasure of curved p-conjugated systems, but also from the fact that they contribute to fundamental research of aromaticity, 12 complexation with molecules and metal ions, 13,14 and strain energy. 1,15,16 It is known that the introduction of heteroatoms into a carbon p-conjugated system can dramatically affect its properties.…”
Section: Introductionmentioning
confidence: 99%